Clinical Health Psychology in Medical Settings : a practitioner's guidebook - Belar, Cynthia D.; Deardorff, William W.; American Psychological Association (Washington, DC : American Psychological Association, 1995)
"Practicing psychologists and professional graduate students will find this classic guide invaluable for developing specialized expertise in clinical health psychology. The authors, 30-year veterans in the field, provide an overview of the roles and functions of clinical health psychologists as well as the education, training, personal, and professional issues involved. Chapters on assessment, intervention, and consulting with medical colleagues present nuts-and-bolts strategies, case examples, and down-to-earth advice for effective practice."--BOOK JACKET.
1. Introduction to clinical health psychology -- 2. Becoming a clinical health psychologist -- 3. Clinical health psychology assessment -- 4. Intervention strategies in clinical health psychology -- 5. Pitfalls in practice -- 6. Ethical issues in the practice of clinical health psychology -- 7. Liability risks in clinical health psychology : malpractice claims and licensing board complaints -- 8. Future issues for clinical health psychology -- App. A. Medical abbreviations -- App. B. Journals relevant to clinical health psychology -- App. C. Professional and disease-specific organizations -- App. D. Some medical problems that may present with psychological symptoms.
Includes bibliographical references (p. 235-255) and indexes.
Keywords: Clinical health psychology; Psychology -- Clinical